Verba Transitif dan Intransitif dalam Bahasa Arab - Moch Syarif Hidayatullah (Alfaz (Arabic Literatures for Academic Zealots), 2013)
Arabic words are distinguished from each other by their three forms:1) ism, noun, which consists of definite and undefinite noun; 2) fiʻl,verb that consists of: a) fiʻl mâdhî: past form, fiʻl mudhâriʻ: presentand future form, fiʻl amr: imperative form, b) mutaʻaddî and lâzim:respectively transitive and intransitive verb; and 3) harf, particle. Thisarticle focuses on the transitive and intransitive verbs of Arabic.